Effect of Solubilizing Group on the Antibacterial Activity of Heptamethine Cyanine Photosensitizers - Olga Semenova; Dmytro Kobzev; Iryna Hovor; Melad Atrash; Faina Nakonechny; Olesia Kulyk; Andrii Bazylevich; Gary Gellerman; Leonid Patsenker (MDPI AG, 2023)
Antibiotic resistance of pathogenic bacteria dictates the development of novel treatment modalities such as antimicrobial photodynamic therapy (APDT) utilizing organic dyes termed photosensitizers that exhibit a high cytotoxicity upon light irradiation. Most of the clinically approved photosensitizers are porphyrins that are poorly excitable in the therapeutic near-IR spectral range. In contrast, cyanine dyes function well in the near-IR region, but their phototoxicity, in general, is very low. The introduction of iodine atoms in the cyanine molecules was recently demonstrated to greatly increase their phototoxicity. Herein, we synthesized a series of the new iodinated heptamethine cyanine dyes (ICy7) containing various solubilizing moieties, i.e., negatively charged carboxylic (ICy7COOH) and sulfonic (ICy7SO3H) groups, positively charged triphenylphosphonium (ICy7PPh3), triethylammonium (ICy7NEt3) and amino (ICy7NH2) groups, and neutral amide (ICy7CONHPr) group. The effect of these substituents on the photodynamic eradication of Gram-positive (S. aureus) and Gram-negative (E. coli and P. aeruginosa) pathogens was studied. Cyanine dyes containing the amide and triphenylphosphonium groups were found to be the most efficient for eradication of the investigated bacteria. These dyes are effective at low concentrations of 0.05 µM (33 J/cm2) for S. aureus, 50 µM (200 J/cm2) for E. coli, and 5 µM (100 J/cm2) for P. aeruginosa and considered, therefore, promising photosensitizers for APDT applications. The innovation of the new photosensitizers consisted of a combination of the heavy-atom effect that increases singlet oxygen generation with the solubilizing group's effect improving cell uptake, and with effective near-IR excitation. Such a combination helped to noticeably increase the APDT efficacy and should pave the way for the development of more advanced photosensitizers for clinical use.